2021
DOI: 10.7759/cureus.12943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Early Impact of the COVID-19 Pandemic on Sports Surgery Fellowship Education

Abstract: Purpose The COVID-19 pandemic forced many hospitals to cancel elective surgeries to minimize the risk of viral transmission and ensure the availability of vital health resources. The unintended consequences of this action on the education and training of orthopaedic sports surgeons are unknown. The purpose of this study is to measure the impact of COVID-19 on orthopaedic sports surgery fellows, their education and training, and their readiness for practice. Methods A comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The majority of the studies were published in countries severely affected by the pandemic, and therefore, medical education and residency training were substantially affected in these countries. Fewer elective operations because of policies established during the pandemic were noted in some specialties, such as urology, orthopedics, plastic surgery, and diagnostic angiography [ 12 , 63 65 ]. The policies of lockdown and quarantine reduced patient volume for some diseases, such as trauma and infectious diseases, which induced less clinical exposure [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were published in countries severely affected by the pandemic, and therefore, medical education and residency training were substantially affected in these countries. Fewer elective operations because of policies established during the pandemic were noted in some specialties, such as urology, orthopedics, plastic surgery, and diagnostic angiography [ 12 , 63 65 ]. The policies of lockdown and quarantine reduced patient volume for some diseases, such as trauma and infectious diseases, which induced less clinical exposure [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical specialties were the most and first affected. Elective surgeries were cancelled or postponed during the pandemic, providing less practice and experience for the residents [ 63 65 , 67 ]. Additionally, residents in surgical specialties were redeployed to manage patients with COVID-19 or perform other work due to medical resource reallocation, disrupting their original surgical training courses.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of evidence related to the use of innovative assessment methods. Though many articles [ 19 , 20 ] have discussed methods to improve orthopaedic education, no study has addressed the question of the practical application of knowledge of undergraduate medical students in orthopaedics.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five percent of the spine fellows were concerned about job opportunities [12]. A similar survey of sports medicine fellows yielded similar responses [11]. A survey from Ireland showed that 35% of trainees felt that their training should be extended to fulfill the training requirements [13].…”
mentioning
confidence: 90%
“…Another variable was the training service where the trainee was enrolled. When spine fellows and sports medicine fellows were surveyed for the effect of the pandemic, 62.2% of spine fellows compared to 80.4% of sports fellows reported > 50% reduction in the number of cases they operated upon due to cancellation of elective surgery [11,12]. A study from Ireland indicated that elective surgery was significantly reduced during the lockdown.…”
mentioning
confidence: 99%